Acute mountain sickness is not related to cerebral blood flow: a decompression chamber study - Baumgartner, Ralf W.; Spyridopoulos, Ioakim; Bärtsch, Peter; Maggiorini, Marco; Oelz, Oswald (Journal of applied physiology, 1999)
To evaluate the pathogenetic role of cerebral blood flow (CBF) changes occurring before and during the development of acute mountain sickness (AMS), peak mean middle cerebral artery flow velocities (V¯¯¯MCAV¯MCA<mover accent="true">V¯</mover>MCA) were assessed by transcranial Doppler sonography in 10 subjects at 490-m altitude, and during three 12-min periods immediately (SA1), 3 (SA2), and 6 (SA3) h after decompression to a simulated altitude of 4,559 m. AMS cerebral scores increased from 0.16 ± 0.14 at baseline to 0.44 ± 0.31 at SA1, 1.11 ± 0.88 at SA2(P < 0.05), and 1.43 ± 1.03 at SA3(P < 0.01); correspondingly, three, seven, and eight subjects had AMS. Absolute and relativeV¯¯¯MCAV¯MCA<mover accent="true">V¯</mover>MCA at simulated altitude, expressed as percentages of low-altitude values (%V¯¯¯MCAV¯MCA<mover accent="true">V¯</mover>MCA), did not correlate with AMS cerebral scores. Average %V¯¯¯MCAV¯MCA<mover accent="true">V¯</mover>MCA remained unchanged, because %V¯¯¯MCAV¯MCA<mover accent="true">V¯</mover>MCAincreased in three and remained unchanged or decreased in seven subjects at SA2 and SA3. These results suggest that CBF is not important in the pathogenesis of AMS and shows substantial interindividual differences during the first hours at simulated altitude.